Towards a reporter system to identify regulators of cross-talk between salicylate and jasmonate signaling pathways in Arabidopsis - Koornneef, Annemart (Landes Bioscience, 2008)
The plant signaling hormones salicylic acid (SA) and jasmonic acid (JA) are regulators of inducible defenses that are activated upon pathogen or insect attack. Cross-talk between SA- and JA-dependent signaling pathways allows a plant to finely tune its response to the attacker encountered. In Arabidopsis, pharmacological experiments revealed that SA exerts a strong antagonistic effect on JA-responsive genes, such as PDF1.2, indicating that the SA pathway can be prioritized over the JA pathway. SA-mediated suppression of the JA-responsive PDF1.2 promoter was exploited for setting up a genetic screen aiming at the isolation of signal transduction mutants that are impaired in this cross-talk mechanism. The PDF1.2 promoter was fused to the herbicide resistance gene BAR to allow for life/death screening of a population of mutagenized transgenic plants. Non-mutant plants should survive herbicide treatment when methyl jasmonate (MeJA) is applied, but suppression of the JA response by SA should be lethal in combination with the herbicide. Conversely, crucial SA/JA cross-talk mutants should survive the combination treatment. SA effectively suppressed the expression of the PDF1.2::BAR transgene. However, suppression of the BAR gene did not result in suppression of herbicide resistance. Hence, a screening method based on quantitative differences in the expression of a reporter gene may be better suited to identify SA/JA cross-talk mutants. Here, we demonstrate that the PDF1.2::GUS reporter will be excellently suited in this respect.